The kinetic-segregation model: TCR triggering and beyond - Davis, S; Van Der Merwe, P (2006)
How the T cell receptor engages antigen is known, but not how that 'triggers' intracellular signaling. The first direct support for a mechanism based on the spatial reorganization of signaling proteins, proposed 10 years ago and referred to as the 'kinetic-segregation' model, is now beginning to emerge, along with indications that it may also apply to the triggering of nonclonotypic receptors. We describe here the development of the model, review new data and suggest how the model fits a broader conceptual framework for receptor triggering. We also consider the capacity of the model, versus that of other proposals, to account for the established features of TCR triggering. © 2006 Nature Publishing Group.